Muamalat Bank Mosque Management Training ‘’The Best Social Marketing’’ Viewed From Public Relations Theories - Anggaraksa Adwitiya Arrazy; Juan Malik Frederick Turpyn (Avant Garde, 2021)
The development of Information and Communication Technology makes it easier for humans to carry out their daily activities. Every element of society can certainly move to create a better human life. One of them is Bank Muamalat. This company helps mosques in Java and Sumatra in carrying out mosque management activities. This study also aims to analyze and examine descriptively the management of the Muamalat Bank mosque which was awarded as "The Best Social Marketing" which was reviewed through Public Relations theories. This research was conducted using a qualitative approach, and the data obtained are the real conditions that occur in the field. And the method chosen is descriptive qualitative method, that is descriptive data which results in the form of written or oral words from people or observed behavior. The results of observations on the management of the Muamalat Bank mosque that there are activities that try to utilize technology through trainings held by the Muamalat Bank itself and in collaboration with the National Amil Zakat Agency (BAZNAS) to train mosque management to develop in the digital era such as now.